Enhanced viability of Lactobacillus spp. via encapsulation in hyaluronan/PVA hybrid electrospun composites for vaginal drug delivery - Margaret O. Ilomuanya; Deborah A. Ogundemuren; Peace-OfonAbasi O. Bassey; Bukola A. Oseni; Adeola T. Kola-Mustapha; Dimitrios Tsamos; Tsamis Alkiviadis; Alexandros E. Tsouknidas; Andrew N. Amenaghawon (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background Vaginal dysbiosis, a change in the beneficial vaginal microbiome, leads to a significant depletion in the essential lactobacilli thus increasing the possibility of vaginal infections such as bacterial vaginosis. Probiotics have gained more attention as a means of delivering exogenous lactobacilli but one of the challenges in delivery strategies is maintaining and improving their viability. The objective of this study is to enhance the viability of Lactobacillus spp., via encapsulation in hyaluronic acid/polyvinyl alcohol hybrid electrospun nanofibers. Polyvinyl alcohol (PVA) and hyaluronic acid (HA) composite nanofibers integrated with Lactobacillus spp. were fabricated by electrospinning. The survival of Lactobacillus spp. after its immobilization in electrospun nanofibers with polyvinyl alcohol and hyaluronic acid was evaluated. Results Scanning electron microscopy indicated larger average diameters in PVA/HA nanofibers with Lactobacillus spp. encapsulation (0.189 ± 0.041 µm to 0.231 ± 0.061 µm between D3 and D4, and 0.177 ± 0.043 µm to 0.212 ± 0.041 µm between D5 and D6) which showed that the nanofibers had the bacterial cells successfully enclosed in them. The viability of the lactic acid bacteria enclosed in the PVA/HA nanofibers was observed to decrease by more than 2-log units. Conclusion The electrospun nanofiber-based delivery system is promising for the encapsulation and delivery of lactic acid bacteria to the vagina to combat recurrent vaginal infections such as bacterial vaginosis.